Occupational Outcomes and Revision Rates for Medial Unicondylar Knee Arthroplasty in U.S. Military Servicemembers - Rodriguez, Marina; Heida, Ken; Rider, Danielle E.; Goodman, Gens P.; Waterman, Brian R.; Belmont, Philip J., Jr. (The Journal of Knee Surgery, 2021)
This study evaluates return to work and revision rates for medial unicondylar knee arthroplasty (UKA) in a high-demand military cohort. Patient demographic and clinical variables were isolated from the medical records of active-duty military servicemembers with at least 2 years of postoperative follow-up and correlated with return to work, medial UKA survivorship, and perioperative complications. The medial UKA annual revision rate was calculated as the percentage of implants revised per observed component year. A total of 39 servicemembers underwent 46 primary medial UKAs (32 unilateral and 7 bilateral) with a mean follow-up of 3.9 (2.0–6.6) years. At a minimum of 2 years postoperatively, 33 (85%) servicemembers returned to military service or successfully completed their service obligation. Older servicemembers (odds ratio [OR] = 0.67; 95% confidence interval [CI]: 0.45, 0.99) had a significantly decreased OR for knee-related medical separation. Nine servicemembers (20%) had conversion to TKA at an average of 2.4 (range, 0.6–5.6) years with a medial UKA annual revision rate of 5%. When compared with Navy/Air Force, Army/Marine servicemembers had an increased TKA conversion rate (OR = 5.40; 95% CI: 1.13, 25.81). Older age decreased the likelihood of medical separation and Army/Marines service was the sole risk factor associated with conversion to TKA. The level of evidence is IV, therapeutic case series.
Keywords: unicompartmental knee arthroplasty; work; military; occupation; functional outcomes